Emigração Cearense entre 1888 e 1915: sentidos, controle e configuração social dos migrantes - Braga Neto, Edgar (2012)
This work aims to make a critique of the cearense emigration from the senses and meanings that were attributed to this emigration and emigrants by the Government and society. The object of study, limited in the late nineteenth and early twentieth century, more precisely, between 1888 and 1915, a period of intense emigration to the South and to the western states of the North, demanded a historical – sociological research in documents with records and narratives related to the phenomenon in the period under study. It is through the so called “mutual interpenetration” between history and sociology that we seek to problematize the senses and meanings attributed to the cearense emigration, giving attention to the forms of social control organized by the Government to terminate with populacional displacement. This way, the category of social configuration, in the formulation of the German sociologist Norbert Elias, led us the necessary theoretical support for the contextualization of this investigate field. Therefore, we built a sociological criticism about this historical process of the cearense emigration, rescuing Key dimensions of the object of study: senses and meanings present in the different communicative vehicles of the epoch; explicit process about the phenomenon of emigration; quantification of emigrations who left during this historical period; and policy of social control that was adopted by the Government to secure the population of Ceará. For that reason, consequently, the criticism of the cearense emigration developed from theoretical and methodological tessituras between history and sociology, has made room to perceive and discuss certain issues to open analytical processes, for example: the emigration to the South of cearense people was not configured properly due to resizing of European and Asiatic imigrantismo; agrarian oligarchies of the country competed for the cearense work force; the concept of retirante is insufficient to represent the fractions of the social group of migrants, and the phenomenon of nomadism has no relation with the emigration cearense people. In fact, we designed this critical work of the cearense emigration, taking into consideration the tension between the different senses and meanings socially produced for understanding of this phenomenon in the course of the history of Ceará.